O impacto dos transtornos mentais no trabalho : resultados do estudo epidemiológico de transtornos mentais São Paulo Megacity - França, Mariane Henriques (2014)
The aims of this study is to estimate the prevalence of mental disorders according to employment status by gender, analyse associations of mental disorders and employment status, and identify the association between treatment seek and employment status among respondents with mental disorders. Moreover, we will estimate the work loss days due to absenteeism and presenteeism, and your association with mental disorders, in the working respondents. Data was analyzed from the São Paulo Megacity Mental Health Survey, a population-based study assessing mental disorders on a probabilistic sample of 5,037 adult residents in the São Paulo Metropolitan Area, using the World Mental Health Survey version of the Composite International Diagnostic Interview. The sample was divided into groups according to employment status, working, economically inactive, and unemployed. The prevalence of mental disorders estimatives were stratified by sex as well, associations with employment status, socio-demographics characteristics, and treatment seek. The mean number of absenteeism and presenteeism in working population was estimate based on the World Health Organization Disability Assessment Schedule. Population-level effects and financial burden were analised. The associations were measured by Odds Ratio using multinomial logistic regression model. The sample was composed by 63% working, 25% inactive, and 12% unemployed. Working was associated to men, younger, higher education and income. Most men were working (75%), while 50% of women were working and 40% were economically inactive. Women show higher prevalence of mood and anxiety disorders. Men presented magnitude of association between any mental, mood and anxiety disorders, and economically inactive or unemployed. Working men shows higher prevalences of impulse-control and substance use disorders. Working women and inactive men had higher mental disorders prevalence. Among respondents with mental disorders, economically inactive respondents were associated to seek general and mental treatment. Any mental disorder was associated with 26.8 loss days due to absenteeism, 92.2 due to presenteeism, and 125.9 total work loss days. The total work loss per year were costs estimated at R$ 2,6 billion per year, corresponding R$ 690 million per year due to absenteeism and R$ 1,9 billion per year due to presenteeism. Our findings provide news epidemiological information about mental disorders and these impacts on work should be considered in establishing priorities for the allocation of health care and resources.